Macroanatomical investigations of the skulls of both genders of Heliosciurus gambianus (Gambian sun squirrel) and Funisciurus anerythrus (Thomas’s rope squirrel) - Olumayowa Olawumi Igado; Omowumi Moromoke Femi-Akinlosotu; Afeez Olumide Akibu (Journal of Basic and Applied Zoology, 2023)
Abstract Background The skull shape and morphometry have been used by several researchers to differentiate and classify species, breeds and also to age the specimen. This study highlights details of the gross morphometry of the skulls of two species of squirrels, Heliosciurus gambianus and Funisciurus anerythrus, using both sexes. Results A total of thirty-one (31) linear morphometric parameters were measured on each skull specimen, relating to individual bones. Results were presented as mean ± standard deviation with significant difference at (P < 0.05). Linear measurements were similar in both genders, although some were negligibly higher in females (51.61% in H. gambianus, 70.96% in F anerythrus); no statistically significant difference was observed (P > 0.05). In spite of the similarity in shape, size and linear morphometric values obtained in both species, Pearson’s correlation analysis of the skull height with other measured parameters gave widely differing results. Correlation data obtained may be used to understand better the pattern of the skull development in these squirrels, as well as how it differs from those obtained in other mammals. Examination of the dentition revealed a varied dental formula across the two species, relating to the presence or absence of the upper and lower premolars. Conclusions The results obtained in this study may find application in the fields of comparative anatomy and forensics as well as provide basis for future research in ageing, skull development and feeding patterns in these species.